Impact of Women Leadership and ESG Ratings and in Organizations: A Time Series Segmentation Study - Dwijendra Nath Dwivedi,; Gattaiah Tadoori,; Saurabh Batra, (Journal of Management Research, 2024)
While many ESG measures focus on factors that influence an organization's bottom line, some do not consider the role of women in leadership. First, we want to perform a time series segmentation study to identify the clusters of companies that have improved the ESG scores over the years and also the cluster of companies that has not been able to do so. Second, we want to test the assumption that businesses with more women directors make better decisions than those with more men. The difference in ESG ratings between companies with and without women on their boards isn’t particularly substantial, and it is unclear what the exact impact of a woman’s inclusion on a board is. A direct link exists between an organization's ESG rating and the composition of its board of directors. We want to verify empirically that companies with gender-diverse boards perform higher on the ESG index than companies with less diversity. The ESG rating reflects three dimensions of sustainable business development. Listed companies with more women on their boards are expected to perform better across all three GSS categories. The idea is that by including a female board member on your board, organizations will be making a positive impact on the lives of the people who work for the organization.